2007
DOI: 10.1051/0004-6361:20066206
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the B[e] star Hen 3-1191 at 10 $\mathsf{\mu}$m with VLTI/MIDI

Abstract: We report spatially resolved, spectrally dispersed N-band observations of the B[e] star Hen 3-1191 with the MIDI instrument of the Very Large Telescope Interferometer. The object is resolved with a 40 m baseline and has an equivalent uniform disc diameter ranging from 24 mas at 8 µm to 36 mas at 13 µm. The MIDI spectrum and visibilities show a curvature which can arise from a weak silicate feature in which the object appears ≈15% larger than in the continuum, but this could result from a change in the object's… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
(79 reference statements)
2
13
0
1
Order By: Relevance
“…This is consistent with scattering in an optically thin disk in Hen 3-1191. Lachaume et al (2007) resolved Hen 3-1191 at N band (8-13 μm) with VLTI/MIDI and found a disk PA of 1 • ±4 • .…”
Section: Hen 3-1191mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with scattering in an optically thin disk in Hen 3-1191. Lachaume et al (2007) resolved Hen 3-1191 at N band (8-13 μm) with VLTI/MIDI and found a disk PA of 1 • ±4 • .…”
Section: Hen 3-1191mentioning
confidence: 99%
“…5 high angular resolution (24-36 mas) of the data in Lachaume et al (2007), which maps the more interior disk region.…”
Section: Hen 3-1191mentioning
confidence: 99%
“…These B[e] stars were perfect targets for the VLTI instruments MIDI and AMBER and the brightest of them were studied in the last decade : CPD -57 • 2874 (Domiciano de Souza et al 2007), Hen 3-1191 (Lachaume et al 2007), HD 87643 (Millour et al 2009a), HD 62623 (Meilland et al 2010), HD 50138 (Borges Fernandes et al 2011, MWC 300 (Wang et al 2012), HD 327083 (Wheelwright et al 2012), V921 Sco , and HD 85567 (Wheelwright et al 2013). Most of these study modeled either with simple geometric model or radiative transfer code such as MC3D, conclude that the dust was located in a circumstellar disk and that the gaseous emission was coming from structures smaller than the dusty-disk inner rim.…”
Section: Mass Loss and Circumstellar Environmentsmentioning
confidence: 99%
“…The next step after the toy models for the physical characterisation of the astrophysical objects can be made from the pure geometrical model towards the self-consistency by including and parameterising the object emissivity in the analysis. For instance, Lachaume et al (2007) and Malbet et al (2005) use optically thick (i.e. emitting as black bodies) and infinitely thin discs to model the circumstellar environment of pre-mainsequence and B[e] stars.…”
Section: Introductionmentioning
confidence: 99%